Do feeding responses of a non-native bivalve outperform the native one in a coastal lagoon? A possible explanation for the invasion success of the dark false mussel Mytilopsis leucophaeata - Rodrigues,Nathalia; Ribeiro,Danielle; C. Miyahira,Igor; G. M. Portugal,Samira; N. Santos,Luciano; A. F. Neves,Raquel (PeerJ, 2023)
The present study aimed to evaluate and compare feeding responses of the non-native and native bivalves, the dark false mussel Mytilopsis leucophaeata and the scorched mussel Brachidontes darwinianus, respectively, by offering different concentrations of seston from the coastal lagoon where these species coexist after dark false mussel introduction (Rodrigo de Freitas Lagoon, Rio de Janeiro-Brazil). For this purpose, independent laboratory experiments were carried out under five concentrations of seston to test the differences in clearance and ingestion rates of bivalves as a function of increasing concentrations of suspended particulate matter (SPM) on seston. In addition, from the integrated analysis of data obtained in experiments, it can be inferred about the efficiency levels of these species to remove SPM from seston and their effects on water turbidity and nutrient concentrations (total carbon, nitrogen, and phosphorus). Our hypothesis was that the non-native bivalve is more efficient to clear and ingest SPM from seston compared to the native one, which may lead to competitive advantages to the successful invasion of M. leucophaeata in coastal lagoons. Native species did not show a significant difference in clearance and ingestion rates with increasing concentrations of seston. Whereas the non-native bivalve showed a slight tendency to increase its clearance and ingestion rates with the increase in seston concentrations, evidencing its plasticity to adjust its feeding responses. The native bivalve was significantly more efficient to clear and ingest SPM at the lower seston concentration (i.e., close to natural concentrations found in the lagoon) compared to the non-native bivalve, which, on the other hand, showed a significant increase in its ingestion rates at the higher concentration tested (140 mg SPM L−1). Thus, the present results did not suggest food competition between the non-native M. leucophaeata and the native B. darwinianus in the introduced system. However, M. leucophaeata increased its feeding response with experimental increment in seston concentration, which suggests species ability to benefit from conditions of increased inputs of organic matter and higher primary production that could mediate its establishment in introduced systems.
Keywords: Invasive species; Coastal lagoon; Clearance rate; Ingestion rate; Seston; Experimental ecology; Dreissenidae